International marketing in the fast changing world - Sto<U+0308>ttinger, Barbara; Schlegelmilch, Bodo B.; Zou, Shaoming (Advances in international marketing ;, 2015)
Volume 26 of Advances in international marketing is devoted to a set of papers that attempt to develop new knowledge or refine the existing knowledge to account for the emerging international marketing issues in a fast changing world. These include topics such as dynamic capabilities of international marketers, entrepreneurial orientation, rise of emerging markets MNCs, cultural and institutional distances, organizational learning and knowledge transfer in MNCs, and international marketing strategies in fast changing environments. Collectively, the papers in Volume 26 shed significant light on many emerging issues and form a solid foundation for future research.